Movement of individual humpback whales between wintering grounds of Oceania (South Pacific), 1999 to 2004 - Garrigue, Claire; Constantine, Rochelle; Poole, Michael; Hauser, Nan; Clapham, Phil; Donoghue, Michael (J. Cetacean Res. Manage., 2020)
The movement of individual humpback whales between regional breeding grounds of Oceania (South Pacific) was documented by individual identification photographs collected from 1999 to 2004. Photographs were collected with comparable effort across the six years in four primary island breeding grounds: New Caledonia, Tonga (Vava’u) the Cook Islands and French Polynesia (Mo’orea and Rurutu); with smaller effort in adjacent regions: Vanuatu, Fiji, Samoa, Niue and American Samoa. Interchange among wintering grounds was assessed first with all usable photographs included in each regional catalogue, representing 1,080 regional sightings (including within-region and between-region resightings) of 949 individual whales from Oceania. From this, 28 cases of movement between (mostly adjacent) regions were documented. Previously undocumented interchange was found between regions of central Oceania and the western South Pacific. No individual was sighted in more than two regions during this six-year period. The documented movement between regions was one-directional, except for one individual sighted first in French Polynesia, then in American Samoa and then back in French Polynesia (each in different years). Only one whale was resighted in more than one region during the same winter season. No directional trend was apparent and movement between regions did not seem to be sex specific. A systematic quality control review of all catalogues was then implemented to calculate standardised indices of within-region return and betweenregion interchange, resulting in a quality controlled catalogue of 776 regional sightings of 659 individuals. The standardised indices confirmed that the probability of between-region interchange was low, relative to within-region return, supporting the assumption of multiple management units or stocks in Oceania. The relative isolation of breeding regions and the movement of individuals across the longitudinal borders of Antarctic management Areas V and VI has important implications for the allocation of historical catches from the Antarctic and therefore, for assessing current levels of recovery for breeding stocks